2017
DOI: 10.1136/jramc-2016-000733
|View full text |Cite
|
Sign up to set email alerts
|

Blast injury of the ear by massive explosion: a review of 41 cases

Abstract: Blast injuries of the ear are characterised by significant functional signs and are not correlated to otoscopic examinations. Sensorineural hearing loss is almost immediately final. When deciding on initial management, the status of the tympanic membrane does not provide any information about the risk of a primary blast injury of the lung; laryngeal nasofibroscopy seems a more relevant screening test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 35 publications
0
18
0
1
Order By: Relevance
“…Perforation had low sensitivity for predicting serious or occult primary blast injury and, as such, was not a reliable biomarker [ 38 ]. Moreover, this and other studies have also shown that the absence of eardrum perforation does not appear to exclude other serious primary blast injuries [ 39 , 40 ].…”
Section: Historical Observations On Blast Injuries and Bintmentioning
confidence: 68%
“…Perforation had low sensitivity for predicting serious or occult primary blast injury and, as such, was not a reliable biomarker [ 38 ]. Moreover, this and other studies have also shown that the absence of eardrum perforation does not appear to exclude other serious primary blast injuries [ 39 , 40 ].…”
Section: Historical Observations On Blast Injuries and Bintmentioning
confidence: 68%
“…6 Incidence of TM perforations in earlier studies has been reported as 16 -90%. [7][8][9][10][11] In our study, 55.47% of all surviving injured victims had evidence of ear trauma in the form of SNHL alone or with TM perforation. This is quite high and may be explained by higher quantity and high explosive nature of the material used in IEDs used in our area.…”
Section: Discussionmentioning
confidence: 95%
“…In the study by Ballivet et al, tympanoplasty was successful only in 44% cases. 11 The incomplete closures were with large perforations, those with foreign bodies (shrapnel), and in 1 with postoperative water exposure. 14…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review by our French military colleagues into blast ear has demonstrated that the significant functional signs caused by such events, but more interestingly that such signs are not correlated to otoscopic examinations 5. Blast Injury has been a significant source of morbidity for UK service personnel and significant research in terms of active ear prevention is still required before an acceptable form of personal protective equipment is found 6.…”
mentioning
confidence: 99%